Optimizing Digital Forensic Workflows for Efficient Cybercrime Investigation Processes - Istri Wulandari (Universitas Negeri Semarang, 2025)
Digital forensic workflows have become critical in modern cybercrime investigations due to the increasing complexity, volume, and volatility of digital evidence. This study examines the structure, effectiveness, and operational challenges of standardized digital forensic workflows across law enforcement environments. Using a mixed-methods approach consisting of workflow simulations, performance evaluation of forensic tools, and interviews with 32 forensic practitioners, this research identifies key procedural bottlenecks and proposes an optimized workflow model. Quantitative data demonstrate that structured workflows reduce evidence processing time by 28% and increase extraction accuracy from 63% to 88%, particularly when automation and triage tools are applied during the initial phases of analysis. Qualitative results reveal that practitioners rely heavily on standardized protocols for chain-of-custody documentation, imaging integrity, and artifact validation. However, challenges persist in tool interoperability, encrypted data extraction, and cross-platform evidence correlation. The study concludes that digital forensic workflows must balance technical rigor with operational flexibility, integrating automation, standardized procedures, and cross-departmental coordination. Contributions to forensic science include a refined workflow framework, identification of critical performance indicators, and operational recommendations for enhancing the reliability and reproducibility of digital investigations.